2013
DOI: 10.1007/s00125-013-2864-6
|View full text |Cite
|
Sign up to set email alerts
|

Fasting proinsulin levels are significantly associated with 20 year cancer mortality rates. The Hoorn Study

Abstract: Aims/hypothesis Proinsulin is possibly associated with cancer through activation of insulin receptor isoform A. We sought to investigate the associations between proinsulin and 20 year cancer mortality rates. Methods The study was performed within the Hoorn Study, a population-based study of glucose metabolism in individuals aged 50-75 years in the Dutch population. Fasting proinsulin levels were measured twice by a doubleantibody radioimmunoassay. Participants were continuously followed to register mortality;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Furthermore, tumor suppressor genes, point mutations, genetic instability, and responses of cells to growth stimulating hormones, such as IGF, may differ by CRC subsite [11]. As it is hypothesized that both diabetes and CRC involve over-expression of both the insulin and IGF receptors [32], this potentially even more complicates the association. Epidemiological evidence also links hyperinsulinemia to changes in sex steroids [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tumor suppressor genes, point mutations, genetic instability, and responses of cells to growth stimulating hormones, such as IGF, may differ by CRC subsite [11]. As it is hypothesized that both diabetes and CRC involve over-expression of both the insulin and IGF receptors [32], this potentially even more complicates the association. Epidemiological evidence also links hyperinsulinemia to changes in sex steroids [33].…”
Section: Discussionmentioning
confidence: 99%
“…At present, disproportional hyperproinsulinemia has been found in the individuals of type 2 diabetes (25,26), impaired glucose tolerance (27,28), and even nondiabetic first-degree relatives of the families with those with type 2 diabetes (29). In addition, several studies have shown that disproportionately elevated proinsulin is associated with all-cause and cardiovascular mortality (30), obesity (31), hepatic steatosis (32), and cancer mortality rates (33). Therefore, it is highly necessary to monitor the proinsulin to insulin ratio in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that peripheral insulin resistance induces a compensatory hypersecretion of insulin by the pancreas. Indeed, the largest epidemiological studies on this subject have identified hyperinsulinemia (or circulating C‐peptide or proinsulin) as a specific prognostic factor for cancer‐related mortality (Ma et al ., ; Wolpin et al ., ; Perseghin et al ., ; Walraven et al ., ). We have therefore simulated the normal and T2DM models as previously described, but with increasing levels of insulin (for each simulation, initial condition for insulin set to 0, 0.5 and 1) as the unique changing parameter.…”
Section: Resultsmentioning
confidence: 97%
“…The ratios of dT under hyperinsulinemia (insulin level = 1) compared to the 0.5 or 0 insulin levels are 1.56 and 2.39, respectively (dT insulin_1 /dT insulin_0.5 = 67.6/43.3 = 1.56; and dT insulin_1 /dT insulin_0 = 67.6/28.2 = 2.39). This is very close to the hazard ratios for cancer‐related mortality concerning patients with hyperinsulinemia, ranging between 1.62 and 2.38 (see Materials and methods for details; Walraven et al ., ; Perseghin et al ., ; Wolpin et al ., ; Ma et al ., ). Concerning the T2DM model, insulin level barely modifies the calculated dTs (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation